An Investigation of Customer Awareness with Reference to Green Marketing of Automobiles:An Empirical Study Conducted at Indore, Madhya Pradesh - Thakar, Girish; Joshi, Nitin M.; Chitale, A. K. (Indian Journal of Marketing, 2009)
The first part of this article focuses on detailed literature review in the area of green marketing, as it was felt by the authors that little attempt has been made to understand this area in the Indian context. The second part of the work deals with assessment of awareness for the green automobiles among the customers of various segments in Indore district of Madhya Pradesh. Looking to the adopted methodology, the study is termed as an empirical study. The work includes testing of three hypotheses related to the above objective. Few questions of the questionnaire used in the study have been analyzed and presented in detail to bring out the attitude of customers towards the green automobile. A factor analysis was also carried out to get more insight into the obtained responses to the variables used in the study.The results of this survey are encouraging in the sense, that they reveal significant awareness about green marketing among the customers, and more so in higher age group. They also appear to be ready, to pay a marginal extra price for obtaining a green automobile. It can be concluded that, the product appears to be welcome in rural as well as urban segments, with owners of four wheelers, favoring it more.